Enzymes as Potencial Source for Clean Label Bakery Product: Part 1, Mechanism and Application Single Enzym - Achmadi, Evita Riviani (Journal of Food and Agricultural Product, 2022)
Background: Increased public awareness of consuming healthy food has driven bakery industry to applied production methods and components of food products that are tailored to the market needs. Food product can be positioned as natural, organic, or free from additives/ preservatives which often referred to clean label trend. Bakery industry commonly using chemical emulsifier as component which improve characteristic and quality baked goods. Usage of chemical component is not appropriate with perception of clean label, although it is not yet clear what a clean label exactly means. Chemical emulsifier has potentially negative effect to health such as intestinal inflammation, obesity, metabolic syndrome and glucose resistance based on several research. Food enzyme can be alternative to replace chemical emulsifier and potentially source of clean label bakery product. Therefore, sustainable study was needed to find role single enzym as food additive and processing aid in bakery product application.Scope and approach: This review explain about the role single enzyme application in bakery product which discuss under three main headings include (i) enzyme as food additive and processing aid, ii) Characteristic enzyme to improve bakery product processing (dough mixing, fermentation, baking), sensories properties and appearance iii) Enzyme mechanism and application to enhance bakery product quality. Optimization of the role and function of enzymes can be conduct by enzyme quality validation through baking tests including formulation development, process parameters (dough rheology, handling machine and baking parameter), product appearance and sensory characteristics.Key findings and conclusion: Food enzymes play a role in enzymatic modifications as biodegradable proteins which not affected to nutritional value baked goods. Enzyme technology is a clean process with low energy consumption, low waste production, safe and less toxic working environment. Therefore, enzyme has potential to fulfill clean label trends and encourage researchers and developers in food industry to explore potential use of food enzymes in bakery products. Enzymes which usually used in bakery come from hydrolase class (amylase, protease, hemicellulase, lipase, xylanase and asparaginase), oxidoreductase class (lipoxygenase and glucose oxidase) and transferase class (transglutaminase). Application enzymes in bakery processs have their respective roles according to enzymes specific characteristics. Enzymes has the main role such as improve rheological and functional properties of dough according to baked goods type, enhance quality and characteristics baked goods including volume, crumb texture, color, taste and extend shelf life (antistaling). Sustainable research and development was needed to optimize the role of enzyme in baked goods by several approach such as (i) incorporation enzymes with other ingredients in the food matrix, (ii) parameters which affect to the work of enzymes in food systems (iii) potential of enzyme combinations to improve baked goods quality and (iv) understanding of usage regulation enzymes as food additives and food processing. Keyword: enzyme, clean label, food additive, processing aid, bakery product